Metabolic syndrome and its components in young healthcare professionals working in a university hospital in Dhaka (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Young healthcare professionals (HCPs) are often exposed to stress, shifting duties, and sedentary lifestyles, predisposing them to an increased risk of metabolic syndrome (MetS).Objectives: To assess the prevalence of MetS and its components in young HCPs working in a university hospital in Dhaka.Methods: In this cross-sectional study, 180 young (aged 18-34 years) HCPs were screened by non-probability sampling (39% physician, 61% nurses, 75% female, 49% overweight/obese) as part of a diabetes screening program by Study on Diabetes and Obesity in Young (SODY) group, Department of Endocrinology, Bangladesh Medical University, during Sep’23-Feb’24. The consensus definition developed by the International Diabetes Federation and the American Heart Association/National Heart, Lung, and Blood Institute in 2009 was used to define MetS.Results: Among the young HCPs, 46 of 180 [25.6% (95% CI 19.4-32.6)] had MetS. The physicians had a prevalence of 37%, and nurses 18%. Abdominal obesity was present in 66%, while reduced high-density lipoprotein cholesterol, elevated triglycerides, elevated fasting plasma glucose, and elevated blood pressure were present in 36%, 27%, 13%, and 22% of the participants, respectively. HCPs with MetS had relatively higher age (median, 31 vs. 26 years), higher frequency of male gender (44% vs. 19%), overweight/obesity (91% vs. 48%), and upper monthly income tertiles (48% vs. 31%) compared to the non-MetS group (p